Kadar Sisa Klor Terhadap Nilai MPN Coliform Pada Jaringan Perpipaan PDAM Di Kabupaten Hulu Sungai Utara - Muhammad Rifani; Munawar Raharja; Isnawati Isnawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2016)
Abstract : Study of free chlorine levels with a value of MPN coliform in water piping distribution PDAM Kabupaten Hulu Sungai Utara Year 2016. Provision of safe drinking water must also meet quality requirements which include requirements physical, chemical, bacteriological and radiological. River water one source of raw water for water companies. Perusahaan Daerah Air Minum (PDAM) Kabupaten Hulu Sungai Utara is a provider of clean water. Based on secondary data report PDAM to maintain water quality after processing up to the distribution network PDAM using chlorine disinfection materials. The purpose of this study was to analyze the relationship between the value of the levels of residual chlorine by MPN coliform in the water pipeline distribution network PDAM. This type of research is observational analytic with cross sectional study design. The samples used were water PDAM Kabupaten Hulu Sungai Utara in the distribution network at a distance of 0, 2, 4, and 6 km from the reservoir. The results showed that decreased levels of free chlorine from distance making 0, 2, 4 and 6 km between 1.5 to 0.0 mg / L. Test results showed coliform MPN value is 0 / 100mL. After testing regression analysis the effect of distance on the maximum levels of residual chlorine with R = 0.834 (strong) and regression analysis test the effect of distance to the minimum levels of residual chlorine with R = 0.943 (strong). To test the statistical relationship between the levels of residual chlorine with coliform MPN value was not done because the results of the coliform MPN no difference. All parameters examined in this study meet the requirements under Permenkes No. 492 / Menkes / PER / VI / 2010. Efforts to do is do a jar test dose in increments of water disinfection, to supervise the treatment system and the distribution network piping. Keywords: PDAM water, distance distribution networks, free chlorine, MPN coliform